PEMBELAJARAN DENGAN MODEL KOOPERATIF THINK PAIR SHARE (TPS) DAN PENDEKATAN ILMIAH TERHADAP KEMAMPUAN KONEKSI DAN KOMUNIKASI MATEMATIS PESERTA DIDIK PADA MATERI PERSAMAAN KUADRAT DIKELAS X SMA NEGERI 2 DOLOG SANGGUL T.P 2019/2020 - Pardosi, Fredika Damawati (LPPM Universitas HKBP Nommensen, 2022)
This research is a quasi-experimental type of research. Because, quasi experiments use all subjects in the study group (intract group) to be given treatment, not using subjects taken randomly. The sample in this study were Class X students of SMA Negeri 2 Doloksanggul in the 2019/2020 academic year. The sample withdrawal used in this study is using simple random sampling technique. This study aims to determine the Think Pair Share (TPS) model, so that it can encourage and inspire students to be able to understand, apply, and develop rational and objective thinking patterns in responding to substance or learning material. The results showed that the design of the learning model that had been designed was good for use. Based on the summary in table 4.14, the value of tcount = 1.699 and ttable = 1.693 was obtained. it means that tcount> ttable, then Ha is accepted or H0 is rejected, so it can be concluded that learning with the cooperative think pair share model is better than the scientific approach to students' mathematical communication skills on the material of quadratic equations in Class X SMA Negeri 2 Doloksanggul T.P. 2019/2020.